2019
DOI: 10.1186/s12881-019-0812-0
|View full text |Cite
|
Sign up to set email alerts
|

BRIP-1 germline mutation and its role in colon cancer: presentation of two case reports and review of literature

Abstract: Background Hereditary colon cancer is characterized by the inheritance of an abnormal gene mutation which predisposes to malignancy. Recent advances in genomic medicine have identified mutations in “novel” genes as conferring an increased risk of colorectal cancer. Mutations in the BRIP1 gene ( BRCA1 Interacting Protein C- terminal helicase 1) are known to increase the risk of ovarian and breast cancers, but this genes association with colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
4
24
0
Order By: Relevance
“…In the present study, we tested the hypothesis that BRIP1 can promote both BC cell growth and metastasis. The results of the present study are summarized as follows: (a) structural validation experiments were consistent with our previous findings, 19 showing fivefold overexpression of BRIP1 in all types of BC tumour samples compared with normal/benign breast tissues; (b) functional validation approaches revealed a novel role of BRIP1 in promoting breast tumour cell growth and progression. In fact, siRNA down‐regulation of BRIP1 attenuated significantly cell proliferation by inducing cell cycle arrest.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we tested the hypothesis that BRIP1 can promote both BC cell growth and metastasis. The results of the present study are summarized as follows: (a) structural validation experiments were consistent with our previous findings, 19 showing fivefold overexpression of BRIP1 in all types of BC tumour samples compared with normal/benign breast tissues; (b) functional validation approaches revealed a novel role of BRIP1 in promoting breast tumour cell growth and progression. In fact, siRNA down‐regulation of BRIP1 attenuated significantly cell proliferation by inducing cell cycle arrest.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these observations, our results showed clearly that both the protein and mRNA levels of BRIP1 were overexpressed in various BC cell lines compared with control normal/immortalized and normal/control breast cells, suggesting that BRIP1 might act as an oncogenic driver in BC. Interestingly, previous study revealed the presence of BRIP1 germline mutations in BC patients without any BRCA mutation, suggesting a link between BRIP1 mutations and BC susceptibility 19 . Collectively, although BRIP1 is considered as a tumour suppressor gene, it is amplified in sporadic cancers, 36 thus supporting our previous 7 and current findings, suggesting that BRIP1 amplification in sporadic cancers could explain the oncogenic role of BRIP1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent meta-analysis of 14 studies (45) examining CRC risk in BRCA1/2 carriers concluded that BRCA1 mutation carriers had increased CRC risk (OR=1.49), whereas BRCA2 mutation carriers did not (OR =1.09). BRIP1 was reported to be associated with ovarian (30) and breast cancers (31), and one study suggested its association with CRC development in two cases (46). In our study, pathogenic variants of BRIP1 showed a 3.6 OR, which is higher than BRCA1/2, indicating that it is worth being included on a list of panel sequencing to assess cancer risk, and a carrier with pathogenic variants of BRIP1 should be subjected to CRC screening in addition to ovarian and breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is the third most common cancer diagnosed in the United States, with an estimated 104,610 new cases and 43,340 deaths for 2020 [1]. The development of colon cancers has been related to both somatic and germline mutations [2,3]. In an analysis of familial colon cancer risk-associated SNP haplotypes, the human gene encoding the protein…”
Section: Introductionmentioning
confidence: 99%